The effect of iron on the expression levels of calcium related gene in cisplatin resistant epithelial ovarian cancer cells - Bahire Kucukkaya; Demet Erdag; Fahri Akbas; Leman Yalcintepe (Open Exploration Publishing Inc., 2021)
Aim: Anticancer drugs (chemotherapeutics) used in cancer treatment (chemotherapy) lead to drug resistance. This study was conducted to investigate the possible effect of iron on calcium homeostasis in epithelial ovarian cancer cells (MDAH-2774) and cisplatin-resistant cells of the same cell line (MDAH-2774/DDP). Methods: To develop MDAH-2774/DDP cells, MDAH-2774 (MDAH) cells were treated with cisplatin in dose increases of 5 μM between 0 μM and 70 μM. The effect of iron on the viability of MDAH and MDAH/DDP cells was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide test at the end of 24 h incubation. Results: At increasing iron concentrations in MDAH and MDAH/DDP cells, the mRNA gene of fifteen genes [inositol 1,4,5-triphosphate receptor (IP3R)1/2/3, ryanodine receptor (RYR)1/2, sarco/endoplasmic reticulum Ca2+ ATPase (SERCA)1/2/3, Na+/Ca2+ exchange (NCX)1/2/3, and plasma membrane Ca2+ ATPase (PMCA)1/2/3/4] associated with Ca2+ differences in expression were determined by quantitative reverse transcription-polymerase chain reaction. Changes in IP3R2, RYR1, SERCA2, NCX3, PMCA1, and PMCA3 gene expressions were observed in iron treatment of MDAH/DDP cells, while changes were detected in iron treatment of MDAH cells in IP3R1/2/3, RYR1/2, SERCA1/2/3, NCX2/3, and PMCA1 expressions. Conclusions: This changes in the expression of calcium channels, pumps, and exchange proteins in the epithelial ovarian cancer cell line and in cisplatin-resistant epithelial ovarian cancer cells suggest that iron may have an important role in regulating calcium homeostasis. Due to differences in the expression of genes that play of an important role in the regulation of calcium homeostasis in the effect of iron, drug resistance can be prevented by introducing a new perspective on the use of inhibitors and activators of these genes and thus cytostatic treatment strategies.